The Role of Green Human Resource Management Practices in Green Campus Responsibility - Mou Xuemin; Beni Widarman Bin Yus Kelana; Cao Jie (Kurdish Studies, 2024)
The objective of this study is to examine the role of Green Human Resource Management (GHRM) in the context of green campus responsibility. Green campus responsibility refers to the responsibility of universities or higher education institutions in attaining the objectives of sustainable development. GHRM is a management concept that integrates environmental sustainability with human resource management, aiming to enhance organizational environmental performance through the utilization of GHRM practices. By synthesizing relevant literature, this study explores the key roles and practices of GHRM in the realm of green campus responsibility, encompassing areas such as recruitment and selection, training and development, performance management, reward and recognition, and employee engagement and communication. The findings indicate that the application of GHRM practices enables universities to effectively fulfill their green campus responsibilities and improve their environmental performance and sustainability. Nevertheless, potential challenges and constraints in promoting GHRM practices are identified, and recommendations for future research are proposed to further advance the understanding of the role of GHRM in green campus responsibility.